In vitro antioxidant activity and in vivo photoprotective effect of Theobroma grandiflorum butter emulgels on skin of mice exposed to UVB irradiation - Aparicio-Álvarez, Chabely M.; Espinoza-Salazar, Catherine E.; Del Carpio-Jiménez, Carla (Frontiers in Sustainability, 2023)
Introduction Copoazú seed butter [Theobroma grandiflorum (Wild ex Spreng) K. Schum] is a rich source of fatty acids and polyphenols, active substances with high antioxidant and moisturizing activities with potential applications in the cosmetic industry. Some studies have demonstrated that sun-induced skin damage is partially mediated by oxidative pathways; in fact, there is evidence for the photoprotective roles of antioxidants. Methods We have developed a stable emulgel-type cosmetic formulation using Copoazú seed butter at different concentrations of 5, 10, and 20% and examined the antioxidant activity and the effect of Copoazú seed butter emulgels against UV-induced epidermal damage in mice to verify its use for topical photoprotective products. Results and discussion The antioxidant activity expressed as EC50 values varied from 8.47 ± 0.013 mg/ml to 4.53 ± 0.046 mg/ml for Copoazú seed butter emulgels. In vitro sun protection factor (SPF) assessment showed that Copoazú seed butter emulgel at 20% has the highest SPF of 11.67 ± 0.001, which is acceptable for the sunscreen products development, and these results were corroborated by the in vivo results since the mice were irradiated with UV light and treated with Copoazú seed emulgels and showed minor damage or significantly reduced the severity of the damage and were comparable with the standard photo-protector. The results showed that Copoazú seed butter is a promising compound for photoprotective formulations.